A complicated picture: Media diversity in the case of Google's video search during the pandemic - Qun Wang (Internet Policy Review, 2023)
With the rise of online video content, especially the growth of online video consumption during the early days of the COVID-19 pandemic, this study focuses on Google's video search as an important but understudied platform to explore Google's role in three media diversity areas - format-type diversity, source diversity, and structural-social diversity-in the online video landscape. Findings of this study reveal a complicated picture: on the one hand, Google can expose users to video content alternative to YouTube video, which involves a variety of media and non- media sources; on the other hand, the lack of diversity can be found in the studied areas. In addition, Google-source partnership and the limited presentation of minority sources at the time of a global crisis, this study argues, has profound implications for media diversity. While normative expectations of digital platforms' role in media diversity depend on different understandings of democracy models, media diversity is an important thread of the ongoing debate regarding platform governance. This study sheds light on one video platform, as a case updating our understanding of media diversity in the digital age.
Keywords: 300; Platform governance; Google; Media diversity; Pandemic; Journalism